2015
DOI: 10.1111/1477-8947.12069
|View full text |Cite
|
Sign up to set email alerts
|

People, protected areas and ecosystem services: a qualitative and quantitative analysis of local people's perception and preferences in Côte d'Ivoire

Abstract: The long‐term integrity of protected areas (PAs), and hence the maintenance of related ecosystem services (ES), are dependent on the support of local people. In the present study, local people's perceptions of ecosystem services from PAs and factors that govern local preferences for PAs are assessed. Fourteen study villages were randomly selected from three different protected forest areas and one control site along the southern coast of Côte d'Ivoire. Data was collected through a mixed‐method approach, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…They attach much value to natural capital, natural processes, and cultural capital on which their livelihoods depend, especially provisioning and cultural services. This is similar to previous research that local residents pay more attention to primary ecosystem services that can be directly enjoyed [4,50,51]. It is expected that direct provisioning services were important for subsistence, but the results also showed that some regulating services, which are critical elements supporting agricultural systems, were also identified, indicating that local people perceive their surroundings as a whole.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They attach much value to natural capital, natural processes, and cultural capital on which their livelihoods depend, especially provisioning and cultural services. This is similar to previous research that local residents pay more attention to primary ecosystem services that can be directly enjoyed [4,50,51]. It is expected that direct provisioning services were important for subsistence, but the results also showed that some regulating services, which are critical elements supporting agricultural systems, were also identified, indicating that local people perceive their surroundings as a whole.…”
Section: Discussionsupporting
confidence: 89%
“…In human-nature interactions, a variety of ecosystem services are produced and flow to local communities, benefiting them in financial or non-financial forms and promoting their overall well-being. However, protected areas, conservation set-asides can also involve the loss of access to natural resources, conflict over their preservation and utilisation, and unequal impacts to different resource users [2][3][4][5][6]. In this context, the well-being of the local rural people is becoming a critical facet for conservation practitioners and managers to understand with a social-ecological systems perspective when designing or evaluating impacts of conservation interventions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This is important because it demonstrates that the majority of households did not recognise the impact land use change occurring today will have on the future, and can mean that actions to support sustainable use or to introduce alternative methods are not taken. This knowledge can help policymakers ensure that policy and project development focuses on enhancing people's awareness about conservation (Amin et al ., ) and sustainable use, alongside the management of ES that have been identified as important to local communities. The need for land use management within Kipembawe is recognised, as illustrated here through householders’ recognition that the loss of ES will have an impact on their households, as well as government attempts to establish land use management plans and protected areas.…”
Section: Discussionmentioning
confidence: 99%
“…There is a short distance from weak approval to opposition, which is why resident's complacency deserves special attention. If the residents are not being compensated for the damages caused or the income lost due to the limitations, this can have a negative effect on their already complicated socioeconomic situation and makes preserving cultural landscapes more difficult (Amin et al, 2015).…”
Section: Results Of In-depth Interviewsmentioning
confidence: 99%